Cultural method for large-scale screening for Chlamydia trachomatis genital infection. - Mallinson, H (1981)
Idoxuridine-treated McCoy cells grown as monolayers in 96 well microplates provide a convenient method for the isolation of Chlamydia trachomatis. Staining of infected monolayers with periodic acid-Schiff reagent (PAS) allows easy recognition of C trachomatis inclusions without the need for dark-ground microscopy. By this method 384 clinical specimens can be examined concurrently. It is sufficiently sensitive to form the basis of a chlamydial culture service for patients attending Sexually Transmitted Diseases (STD) Clinics.